2000
DOI: 10.1091/mbc.11.1.277
|View full text |Cite
|
Sign up to set email alerts
|

The N Terminus of the Transmembrane Protein BP180 Interacts with the N-terminal Domain of BP230, Thereby Mediating Keratin Cytoskeleton Anchorage to the Cell Surface at the Site of the Hemidesmosome

Abstract: In epidermal cells, the keratin cytoskeleton interacts with the elements in the basement membrane via a multimolecular junction called the hemidesmosome. A major component of the hemidesmosome plaque is the 230-kDa bullous pemphigoid autoantigen (BP230/BPAG1), which connects directly to the keratin-containing intermediate filaments of the cytoskeleton via its C terminus. A second bullous pemphigoid antigen of 180 kDa (BP180/BPAG2) is a type II transmembrane component of the hemidesmosome. Using yeast two-hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
87
2
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 39 publications
4
87
2
4
Order By: Relevance
“…Epidermal BPAG1e interacts with the hemidesmosomal proteins α6β4 integrin and collagen XVII in basal keratinocytes and mediates epidermal-dermal cohesion (Borradori and Sonnenberg, 1999;Hopkinson and Jones, 2000;Koster et al, 2003;Leung et al, 2001b;Litjens et al, 2006;Sawamura et al, 1991a,b). In addition, BPAG1e also binds to the epidermal cytokeratin network that is formed by keratins 5 and 14 (K5, K14) in basal keratinocytes and thereby connects them to the extracellular matrix (Fontao et al, 2003;Guo et al, 1995).…”
Section: Cellular Functions Of Bpag1mentioning
confidence: 99%
“…Epidermal BPAG1e interacts with the hemidesmosomal proteins α6β4 integrin and collagen XVII in basal keratinocytes and mediates epidermal-dermal cohesion (Borradori and Sonnenberg, 1999;Hopkinson and Jones, 2000;Koster et al, 2003;Leung et al, 2001b;Litjens et al, 2006;Sawamura et al, 1991a,b). In addition, BPAG1e also binds to the epidermal cytokeratin network that is formed by keratins 5 and 14 (K5, K14) in basal keratinocytes and thereby connects them to the extracellular matrix (Fontao et al, 2003;Guo et al, 1995).…”
Section: Cellular Functions Of Bpag1mentioning
confidence: 99%
“…In the case of the epithelial dystonin-e protein, this most certainly appears to be the case. Dystonin-e plays a wellestablished role of linking keratin intermediate filaments to hemi-desmosomes within keratinocytes [Hopkinson and Jones, 2000]. In the nervous system, no hemidesmosomes or keratin filaments are present, and the domain structure of the major neuronal dystonin (dystonina) isoforms differs greatly from the epithelial isoform (Fig.…”
Section: Dystonin Is Essential To Neurons-but For What?mentioning
confidence: 99%
“…This protein was predicted to be involved in tethering intermediate filaments at the site of hemidesmosomes in the keratinocyte cells of the skin [Sawamura et al, 1991], a prediction later confirmed [Hopkinson and Jones, 2000]. It may be the case that a disruption in the tethering function of BPAG1 results in a breakdown in the mechanical linkage between keratinocytes and the underlying basement membrane.…”
mentioning
confidence: 99%
“…The NH 2 -terminal domain of eBPAG1 is implicated in its recruitment to HDs. This region associates with the cytoplasmic domain of two transmembrane components of HDs, the bullous pemphigoid antigen 2 (BPAG2, also termed BP180) and the integrin ␤4 subunit (9).…”
mentioning
confidence: 99%